2016
DOI: 10.1016/j.jval.2016.03.1932
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Cost Effectiveness Information on the Highest-Cost Drugs and Procedures in the United States

Abstract: Objectives: The SF6D is a preference-based measure designed to calculate QALY. Preference-based measures are standardized multidimensional health state classifications with preference or utility weights elicited from a sample of the population. There is actually a concern that valuations may differ between countries because of differences in culture, thus invalidating the use of values obtained from one country in another. The aim of this article is to assess whether these valuations differ from one country to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…First, efficient reallocation of resources requires that cost-effectiveness be known for both the therapy with spending over the cap and the service/therapy to which spending will be reallocated. A review of US-specific cost-effectiveness analysis in Tuft's Medical Center Cost Effectiveness Analysis Registry, however, found that this information is often missing for both the top procedures and drugs [9], which makes efficient reallocation of resources difficult. For example, cost-effectiveness data for serotoninnorepinephrine reuptake inhibitors, which were present in the list of drugs that exceeded the $904 million spending cap, were either not available or not available in a timely manner (relative to launch).…”
Section: Discussionmentioning
confidence: 99%
“…First, efficient reallocation of resources requires that cost-effectiveness be known for both the therapy with spending over the cap and the service/therapy to which spending will be reallocated. A review of US-specific cost-effectiveness analysis in Tuft's Medical Center Cost Effectiveness Analysis Registry, however, found that this information is often missing for both the top procedures and drugs [9], which makes efficient reallocation of resources difficult. For example, cost-effectiveness data for serotoninnorepinephrine reuptake inhibitors, which were present in the list of drugs that exceeded the $904 million spending cap, were either not available or not available in a timely manner (relative to launch).…”
Section: Discussionmentioning
confidence: 99%